How L34V Mutation Affect the Structure, Dynamics and Aggregation of Amyloid-β40 (Aβ40) Peptide: Key Insights from Molecular Dynamics Simulations - Thakur, Hema (My University, 2018)
Alzheimer’s disease (AD) is a neurodegenerative disease identified by Alois Alzheimer in 1907. AD is characterized by short-term memory loss, disorientation and impairment of judgement. According to amyloid cascade hypothesis, the aggregation of a 39-42 amino acid long peptide, amyloid-β (Aβ) peptide in brain is a major cause of AD. The recent studies demonstrated that L34V mutation changes the lethality, and rate of fibril formation of the wild type (wt) Aβ40 peptide. However, the molecular mechanism behind increase in the wt Aβ40 aggregation on L34V mutation remains unclear. In this regard, the influence of L34V mutation on the structure and dynamics of Aβ40 was investigated using all-atom molecular dynamics simulations. The Aβ40 monomer simulations starting from a random coil conformation highlight that L34V mutation cause noticeable changes in the conformational ensemble as well as in the secondary structure of the Aβ40 peptide. The present investigation provides key physical insights into the increased rate of fibril formation upon L34V mutation and a detail atomistic picture of the L34V induced conformational changes in the wt Aβ40.
Master of Science- Chemistry
Keywords: Alzheimer disease; protein aggregation; L34V mutation; Conformational transition; molecular dynamics